Frequent consulters in general practice: a systematic review of studies of prevalence, associations and outcome. - Gill, D; Sharpe, M (1999)
We conducted a systematic review of the observational literature on frequent consulters in general practice. Electronic searching identified 34 studies which met our inclusion criteria. Frequent consulters were identified in a wide range of primary health care settings, confirming that a small proportion of patients is responsible for a disproportionate number of consultations. A cutoff of 9-14 consultations per annum was used to define a frequent consulter in most studies. Studies have examined a variety of associated characteristics, and indicate that frequent consulters are highly heterogeneous, and have high rates of physical disease, psychiatric illness and social difficulties. Few are likely to conform to the "heartsink" stereotype. These patients are likely to have multiple, complex problems, often including chronic physical disease, with or without psychological and social problems. The natural history of frequent consulting behavior seems to be to persist in many cases. Implications for management are discussed.